2010
DOI: 10.1152/ajpheart.00662.2009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic physical activity mitigates cerebral hypoperfusion during central hypovolemia in elderly humans

Abstract: This study sought to test the hypothesis that orthostasis-induced cerebral hypoperfusion would be less severe in physically active elderly humans (ACT group) than in sedentary elderly humans (SED group). The peak O(2) uptake of 10 SED (67.1 +/- 1.4 yr) and 9 ACT (68.0 +/- 1.1 yr) volunteers was determined by a graded cycling exercise test (22.1 +/- 1.2 vs 35.8 +/- 1.3 ml.min(-1).kg(-1), P < 0.01). Baseline mean arterial pressure (MAP; tonometry) and middle cerebral arterial blood flow velocity (V(MCA); transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Nevertheless, increased vascular volume was not maintained after a 3‐month sedentary period. Other recent studies also underline the beneficial effects of exercise, generally chronic exercise, for cerebral vascularization in both aged (251–254) and non‐aged (255–257) individuals, invariably accompanied by measurable neuroprotective effects (258). In this regard, it is necessary to differentiate between the effects of mild‐to‐moderate exercise over longer periods that increase cerebral flow and those of heavy, strenuous and intensive exercise that reduce cerebral blood flow, as well as individual preferences and circumstances (259–263).…”
Section: Exercise and Angiogenesismentioning
confidence: 96%
“…Nevertheless, increased vascular volume was not maintained after a 3‐month sedentary period. Other recent studies also underline the beneficial effects of exercise, generally chronic exercise, for cerebral vascularization in both aged (251–254) and non‐aged (255–257) individuals, invariably accompanied by measurable neuroprotective effects (258). In this regard, it is necessary to differentiate between the effects of mild‐to‐moderate exercise over longer periods that increase cerebral flow and those of heavy, strenuous and intensive exercise that reduce cerebral blood flow, as well as individual preferences and circumstances (259–263).…”
Section: Exercise and Angiogenesismentioning
confidence: 96%
“…Baseline normoxic data were averaged over 1 min before the first and fifth hypoxic bouts. Five-minute steady-state RRI before day 1 and day 14 hypoxic exposures were analyzed using power spectral analysis (Welch option) after fast-Fourier transform with the data analysis and display program (DADiSP, Cambridge, MA) as previously described (11,17,54). Low-frequency power between 0.04 and 0.14 Hz and high-frequency power between 0.15 and 0.40 Hz of RRI variability were extracted and compared between day 1 and day 14.…”
Section: Participantsmentioning
confidence: 99%
“…More recently, studies have shown that exercise also exerts positive changes on the cerebral vasculature [1, 7, 2328], including preserved CBF in areas associated with aging and AD using ASL [29], higher middle cerebral artery blood flow velocity in young and older adults using transcranial doppler ultrasound [23, 24, 27, 29], and associations between physical fitness, vascular function and cognitive performance in older women [24]. Studies investigating differences in CBF between fit and sedentary individuals have revealed that CBF was 17% higher in highly fit men when compared to sedentary adults [23], and that the systemic circulation benefits of exercise seem to extend to the brain in fit postmenopausal women compared to their sedentary counterparts [24].…”
Section: Introductionmentioning
confidence: 99%